Developing fluency in a language of tactile communication - Tuttle, Neil; Hillier, Susan (Frontiers in Rehabilitation Sciences, 2023)
Touch has been an integral part of physiotherapeutic approaches since the inception of the profession. More recently, advances in the evidence-base for exercise prescription and ‘active’ management have brought ‘touch’ into question. This in part assumes that the patient or recipient simply passively receives the input rather than being an active partner in the interaction. In this chapter we propose that touch can be used as a two-way conversation between therapist and client where each is engaged in a somatic dialogue with the potential to raise patient awareness of, and improvement in, movement-based behaviour.